Bis(3-phenylpropylammonium) dichromate (VI): Synthesis, crystal structure and spectroscopy studies (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The structure of bis(3-Phenylpropylammonium) dichromate(VI) was determined from X-ray diffraction data. The compound crystallizes in the monoclinic system (space group P21/c) with the lattice parameters: a = 7.9379(2) Å, b = 36.2439(16) Å, c = 7.5753(3) Å; B = 96.069(2); V= 2167.20(14) Å3 and Z = 4. The structure was solved from 4959 independent reflections with R = 0.043 and Rw = 0.105. The structure consists of discrete dichromate anions (Cr2O72-) with eclipsed conformation stacked in layers parallel to (a, c) plane at y = 0 and ½. These anions are linked via the 3-phenylpropylammonium cations by N—H…O and C—H…O hydrogen bonds, forming a two-dimensional supramolecular network. Crystal structure and spectroscopic studies are reported for the bis(3-phenylpropylammonium) dichromate(VI).